Falta por Aqui uma Grande Razão (ou Várias Razões Pequenas?): O Chicote da História, o Todo e as Partes nas práticas sociais - Godinho, Paula (Trabalhos de Antropologia e Etnologia, 2020)
different daily life and in moments of crisis. History whips time, as noted by Julio Cortázar, and demands the possible practices, among risks, uncertainties, vacillations and dreams, which are outlined and acted upon by humans, because the future will not be made by cyborgs. Imagined, anticipated, desired or feared, with different formats, in different moments and contexts, the futur is based on experience, which produces expectation, opening itself to the “not yet”, with hope, between the “great reasons” and the current and identical days.